An uncommon case of gouty arthritis in a teenage boy (Bangladesh Journal of Medical Science, 2021)
Joint pain is a common complaint in the paediatric age group with overuse and traumatic injury being the common causes. However, joint pain involving multiple sites, persistent or recurrent, and severe may suggest other diagnoses. One of the possible groups of diagnosis is rheumatology in nature, which is often difficult to diagnose, especially in paediatric patients. Gouty arthritis is a rather uncommon rheumatology problem in children and the diagnosis is often missed at the initial presentation. We report a 16-year-old boy who repeatedly presented with debilitating and alternating polyarthritis, diagnosed and treated as juvenile gouty arthritis after thorough clinical assessment and basic laboratory investigations in a resource-limited primary care clinic.Bangladesh Journal of Medical Science Vol.20(1) 2021 p.200-203